Delivering a Pilot Smoking Cessation Program through the Patient Portal of an Electronic Medical Record (EMR) at a Patient-Centered Medical Home (PCMH) - Amanda M Singrey; Kristin A Casper; Nicole V Brown; Bella H Mehta (University of Minnesota Libraries Publishing, 2016)
Pharmacists are providing clinical services in nontraditional practice settings including the patient-centered medical home (PCMH). PCMHs strive to improve patient outcomes in a number of ways, including through innovative use of health information technology (HIT) and by encouraging patients to take an active role in their health care. This paper describes a pharmacist-directed smoking cessation program at a PCMH that utilizes HIT to engage patients in the smoking cessation process and lessons learned from implementation of the program to guide other pharmacists considering implementing a similar program. Secure messaging through the patient portal of the electronic medical record (EMR) can be an effective way to deliver a smoking cessation program for appropriately selected patients and aligns with PCMH standards as the program uses HIT to engage patients in self-management.   Type: Original Research